Linkages between criteria of trypanotolerance and livestock performance traits in N'Dama cattle in the Gambia. Abstract - Agyemang, K. (Cornell University, 1995)
A total of 505 lactation records from 340 cows of the N'Dama breed were matched with health records recorded on the same animals over a period of 4 years. The objective of the analysis was to establish linkages between 3 criteria of trypanotolerance namely, frequency of infection, control of parasitemia and control of anemia associated with the disease, on one hand, and performance traits: milk offtake, calf weaning weight, calving interval, and a cow productivity index incorporating these traits, on the other hand. The longer term objective is to include one or more of these criteria in a selection index for genetic improvement programs, if found to be associated with performance traits. Least-squares analyses showed that the control of anemia measured by packed red cell volume (PCV) was more frequently linked with performance traits than the other criteria. Infected cows which maintained above-average PCV values had a 84 percent higher (P<0.05) cow productivity index than those with below-average PCV. Uninfected cows achieved a 60 percent higher (P<0.05) cow productivity index than infected cows (64.0 (+ or-) - 5.44 vs. 39.8 (+ or -) - 7.15 kg calf weight/cow/year). It was concluded that the effects observed were large enough to suggest that selection of animals based on some of the criteria will give correlated response in performance traits, provided the criteria have genetic basis.